Efficacy of cannabinoids compared to the current standard treatments on symptom relief in persons with multiple sclerosis (CANSEP trial): study protocol for a randomized clinical trial - Zertal, Amel; Alami Marrouni, Kanza; Arbour, Nathalie; Jutras-Aswad, Didier; Pomey, Marie-Pascale; Rouleau, Isabelle; Prat, Alexandre; Larochelle, Catherine; Beaulieu, Pierre; Chamelian, Laury; Sylvestre, Marie-Pierre; Morin, Danielle; et al. (Frontiers in Neurology, 2024)
Background Multiple sclerosis (MS) is an inflammatory and degenerative disease of the central nervous system. More than 90,000 Canadians are affected; a cure is yet to be found. Available treatments to manage the disease course are only partially effective. For many years, persons with MS (PwMS) have used cannabis to relax, to reduce pain and spasticity, or to improve sleep and daily functioning, despite the lack of scientific evidence on the efficacy of specific cannabinoids [i.e., tetrahydrocannabinol (THC) and cannabidiol (CBD)] on these MS symptoms. The purpose of this clinical trial is to assess the effectiveness of different doses of these cannabinoids, alone or combined, on spasticity relief, compared to placebo. Moreover, we aim to determine which treatment is best effective to address other key MS conditions. Methods A double-blinded, randomized, factorial, placebo-controlled trial will be performed. We intend to include up to 250 PwMS aged over 21 recruited from the Centre hospitalier de l’Université de Montréal MS Clinic. PwMS will be randomly assigned on a 1:1:1:1 ratio to one of the trial arms: THC alone, CBD alone, THC/CBD combination, or placebo, using stratified blocked randomization, with random blocks within each stratum. The primary outcome is a self-assessment of spasticity using the mean Numeric Rating Scale score over 7 days. The main outcome will be the difference in this score at 4 weeks compared to baseline. Secondary outcomes include assessments of spasticity as measured by a clinician, pain, fatigue, sleep, bowel, bladder, and sexual dysfunction, restless legs syndrome, mental health, quality of life, mobility, cognitive functioning, and adverse events. Treatment responders are eligible for a 12-week extension phase, using the same treatment allocation and assessments. Discussion Previous clinical studies examined the efficacy of cannabis-based medicines in PwMS, mostly using products with 1:1 THC/CBD ratio. The major barrier to effectively use cannabis in real-world clinical settings is the lack of evidence on benefits of specific cannabinoids and information on possible related risks. The CANSEP study will contribute to overcome these limitations and identify the risks and benefits of cannabis-based treatments in PwMS. Clinical trial registration ClinicalTrials.Gov, NCT05092191.